2020
DOI: 10.3389/fimmu.2019.03056
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1 (ICAM-1) and ICAM-2 Differentially Contribute to Peripheral Activation and CNS Entry of Autoaggressive Th1 and Th17 Cells in Experimental Autoimmune Encephalomyelitis

Abstract: In experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS), myelin-specific T cells are activated in the periphery and differentiate in T helper (Th) 1 and Th17 effector cells, which cross the blood-brain barrier (BBB) to reach the central nervous system (CNS), where they induce neuroinflammation. Here, we explored the role of intercellular adhesion molecule-1 (ICAM-1) and ICAM-2 in the activation of naïve myelin-specific T cells and in the subsequent migration of differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 67 publications
3
38
0
Order By: Relevance
“…Higher numbers of T cells are seen to cross a monolayer of immortalized mouse brain endothelioma bEnd5 cells, which fail to establish mature TJs, when compared to a monolayer of primary mouse brain microvascular endothelial cells, which retain excellent BBB features during 1 week in culture (46). In the presence of shear flow this in vitro BBB model allows to investigate extended T-cell crawling against the direction of flow, searching for rare sites permissive for diapedesis (47), a unique T cell behaviour on the BBB observed by in vivo imaging studies (48,49). Thus, identification of the molecular mechanisms mediating the multi-step migration of immune cells across the BBB in vitro requires stringent endothelial barrier models best to be combined with sophisticated microfluidics and live cell imaging.…”
Section: Methodological Approaches To Investigate Immune Cell Trafficmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher numbers of T cells are seen to cross a monolayer of immortalized mouse brain endothelioma bEnd5 cells, which fail to establish mature TJs, when compared to a monolayer of primary mouse brain microvascular endothelial cells, which retain excellent BBB features during 1 week in culture (46). In the presence of shear flow this in vitro BBB model allows to investigate extended T-cell crawling against the direction of flow, searching for rare sites permissive for diapedesis (47), a unique T cell behaviour on the BBB observed by in vivo imaging studies (48,49). Thus, identification of the molecular mechanisms mediating the multi-step migration of immune cells across the BBB in vitro requires stringent endothelial barrier models best to be combined with sophisticated microfluidics and live cell imaging.…”
Section: Methodological Approaches To Investigate Immune Cell Trafficmentioning
confidence: 99%
“…In fact, lack of endothelial ICAM-1 and ICAM-2 on a mouse model of the BBB, abrogates Th1 cell polarization and crawling (47,83) supporting the notion that endothelial ICAM-1 and ICAM-2 are essential for mediating the Th1 cell crawling against the direction of flow on the BBB with no additional role of α 4 β 1 /VCAM-1 (47,83). Side-by-side comparison of mouse encephalitogenic Th1 and Th17 cell interaction with the BBB has shown that Th1 cells, in comparison to Th17 cells, arrest in higher numbers on the BBB in vitro and in vivo, however, both Th1 and Th17 cells rely on endothelial ICAM-1 and ICAM-2 for crawling on the BBB (49). Interestingly, genetic ablation of α 4 integrins in mouse T cells blocks Th1 cell entry into the CNS during EAE, while Th17 cells can still accumulate in the brain but not the spinal cord using LFA-1 (85,86).…”
Section: Cd4 + and Cd8 + T Cellsmentioning
confidence: 99%
“…ICAM-1 is a member of the immunoglobulin superfamily of adhesion molecules; these molecules contribute to cell-to-cell contact and cell-to-matrix interactions and are considered to be immune-promoting molecules ( 15 ). ICAM-1 and its receptors are critically involved in various inflammatory pathological diseases, such as experimental allergic encephalomyelitis, rheumatoid arthritis, and GVHD ( 65 67 ). Blockade of ligands or receptors has shown some beneficial effects in controlling these diseases in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…BBB endothelial cells formed a confluent monolayer, characterized by junctional localization of the adherens junction proteins b-catenin and VE-cadherin and of the tight junction proteins zona occludens-1 (ZO-1) and claudin-5 (Supplementary Figures 1A-D). To model neuroinflammatory conditions, BBB endothelial cells were stimulated either with interleukin-1b (IL-1b) or with tumor necrosis factor-a (TNF-a) + interferon-g (IFN-g) (27,28). Cell surface protein expression of the integrin-binding molecule intercellular adhesion molecule-1 (ICAM-1) was specifically upregulated upon IL-1b stimulation as was the endothelial cell adhesion molecule E-selectin, while expression of vascular cell adhesion molecule-1 (VCAM-1) was not affected upon cytokine stimulation compared to unstimulated BBB endothelial cells (Supplementary Figure 1E-J).…”
Section: Functional Characterization Of Primary Cns Barrier and Moc In Vitro Modelsmentioning
confidence: 99%